2003
DOI: 10.1177/02698811030173002
|View full text |Cite
|
Sign up to set email alerts
|

Does the Brain Noradrenaline Network Mediate the Effects of the CO2 Challenge?

Abstract: The inhalation of carbon dioxide (CO2) is commonly used in patients and volunteers as a means of producing anxiety or panic. It is generally believed that patients with panic disorder are more vulnerable to the effects of CO2 than patients with other anxiety disorders or healthy volunteers and there is speculation and debate as to the mechanism for this apparent sensitivity. Recent work from our group has shown that a single inhalation of 35% CO2 activates the hypothalamic-pituitary-adrenocortical (HPA) axis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 61 publications
(66 reference statements)
6
58
3
1
Order By: Relevance
“…There was, however, a striking difference between the two groups with respect to the heart rate response. The expected response, as determined from previous studies of the CO 2 challenge in healthy volunteers, includes initial bradycardia followed by a noradrenaline-mediated increase in total peripheral resistance and a pressor response [15,18]. Although all of the DAN− subjects had a bradycardic response, this was not seen in any of the DAN+ patients.…”
Section: Discussionmentioning
confidence: 90%
“…There was, however, a striking difference between the two groups with respect to the heart rate response. The expected response, as determined from previous studies of the CO 2 challenge in healthy volunteers, includes initial bradycardia followed by a noradrenaline-mediated increase in total peripheral resistance and a pressor response [15,18]. Although all of the DAN− subjects had a bradycardic response, this was not seen in any of the DAN+ patients.…”
Section: Discussionmentioning
confidence: 90%
“…This noradrenergic innervation of the BNST arises probably from the A1 and A2 medullary cell groups (Ungerstedt, 1971;Moore, 1978). These two cell groups are activated by threatening stimuli (Zhu and Onaka, 2002;Bailey et al, 2003). Thus, they might also be activated by predator odors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a study carried out in healthy volunteers reported that a single inhalation of 35% CO 2 increased blood pressure and subjective fear, and activated the HPA axis (Bailey et al 2003).…”
Section: Carbon Dioxide (Co 2 )mentioning
confidence: 97%